An investigation of memory rehabilitation and strategies - Gopi, Yashoda (2023)
Memory is important in our everyday lives and impairment due to acquired brain injury such as stroke or decline with aging can result in difficulties completing daily activities. It is therefore important to understand how memory is assessed and treated and to explore methods to improve ability. In this thesis, I examined how subjective memory ability is evaluated, clinical practices regarding memory after stroke, current approaches to memory rehabilitation, and the efficacy of mnemonic strategies for adults across all ages. A review of subjective memory measures (Chapter 2) revealed a wide range of standardised metamemory questionnaires that can be used in clinical and research settings to examine self-efficacy, complaints, and multiple dimensions of metamemory. However, a survey of healthcare professionals (Chapter 3) demonstrated that memory after stroke is often assessed in clinical settings with non-standardised subjective measures (e.g., patient interviews) in addition to cognitive screens. Additionally, rehabilitation frequently involves the use of various external memory aids and strategies to compensate for deficits. Similarly, a review of memory rehabilitation approaches currently in use (Chapter 4) revealed numerous strategies across the restoration, knowledge-acquisition, compensatory, and holistic approaches that are often combined to form rehabilitation programmes in research settings. An empirical study with young adults (Chapter 5), demonstrated limited efficacy of a commonly used face-name mnemonic strategy to improve name recall, but better outcomes with a simplified version of the mnemonic. In contrast, a study examining the efficacy of the simplified mnemonic across middle-aged and older adults (Chapter 6) revealed no influence of age or mnemonic instruction on name recall. These outcomes have highlighted important considerations for evaluating memory, revealed the various methods available for researchers and clinicians to treat memory impairment, and demonstrated that mnemonic strategies might have limited efficacy for healthy adults across all age groups.